Hydro-pedology of a representative hillslope of a landscape on granite-gneissic bedrock in West Africa (Togo). Relations with the behavior of a cultivated plant. - (:unkn) unknown (My University, 1996)
This study deals with the hydropedological characterization and a first evaluation of the agricultural suitability of a hillslope that is representative of a landscape covering more than 500.000 km 2 in West Africa. This landscape has a tropical climate with one dry season, a savanna vegetation, a granito-gneissic bedrock, and a pedological organization with ferrallitic and ferrugineous soils. The hillslope is located in Togo between 1°00’-1°01’ longitude East and 8°38’-8°39’ latitude North.~The study of the soil sequence permitted to recognize three pedological domains (ferrallitic, ferrugineous and hydromorphic domains). These domains are delimited by slope ruptures, and are associated with several quaternary eroded piedmont slopes. The characteristics and the distribution of 20 pedological horizons allowed to explain the pedological differentiation of the hillslope according to two factors : piedmont slope erosion followed by a partial filling up of downslope; and horizons transformations due to water effects.The study of the hydrosequence has been carried out during 3 years. This revealed the existence of a perched semipermanent water table, which is localized in ferrugineous and hydromorphic domains. This also showed the existence of a deep water table in all the pedological domains.Relations between soil sequence and hydrosequence have been studied : statistical relations have been found between , on the one hand, the annual frequency of water logging, and , on the other hand, the type of horizon and the color of materials.Transposition of results at smaller scales would be possible, using numerical models of landscape.~A first evaluation of the agricultural suitability of this hillslope has been carried out with a cotton cultivation and homogeneous agronomical conditions. This has shown the existence of a sequence of hydropedological constraints : resistance to penetration in ferrallitic domain; low fertility and excess of water due
Keywords: African Research